2018
DOI: 10.1038/s41598-018-21315-y
|View full text |Cite
|
Sign up to set email alerts
|

Tomato AUXIN RESPONSE FACTOR 5 regulates fruit set and development via the mediation of auxin and gibberellin signaling

Abstract: Auxin response factors (ARFs) encode transcriptional factors that function in the regulation of plant development processes. A tomato ARF gene, SlARF5, was observed to be expressed at high levels in emasculated ovaries but maintained low expression levels in pollinated ovaries. The amiRNA SlARF5 lines exhibited ovary growth and formed seedless fruits following emasculation. These parthenocarpic fruits developed fewer locular tissues, and the fruit size and weight were decreased in transgenic lines compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
82
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 72 publications
5
82
0
2
Order By: Relevance
“…We found that all activator SlARFs were expressed around anthesis, and they interacted with SlDELLA in Y2H assays. A recent study showed that amiRNAinduced downregulation of SlARF5 expression resulted in parthenocarpy (Liu et al, 2018). We also showed that besides SlARF7, SlARF5 and SLARF8B were downregulated in the SlARF7 RNAi line.…”
Section: Discussionsupporting
confidence: 57%
“…We found that all activator SlARFs were expressed around anthesis, and they interacted with SlDELLA in Y2H assays. A recent study showed that amiRNAinduced downregulation of SlARF5 expression resulted in parthenocarpy (Liu et al, 2018). We also showed that besides SlARF7, SlARF5 and SLARF8B were downregulated in the SlARF7 RNAi line.…”
Section: Discussionsupporting
confidence: 57%
“…In plants, ARFs encode important transcription factors which regulate the expression of genes in response to auxin ( Guilfoyle and Hagen, 2007 ). Several ARF transcription factor genes have been cloned from Arabidopsis , rice and tomato, and were found to play crucial roles in plant growth and developmental processes ( Harper et al, 2000 ; Waller et al, 2002 ; Ellis et al, 2005 ; Okushima et al, 2005 ; Wilmoth et al, 2005 ; Wang et al, 2011 ; Ren et al, 2017 ; Liu et al, 2018 ). However, there is no report on the ARF transcription factors in improving carotenoid contents and abiotic stress tolerance in plants.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, ARF2 mediated ABA response ( Wang et al, 2011 ); MP/ARF5 regulated embryo and flower patterning and vascular differentiation ( Hardtke and Berleth, 1998 ; Krogan et al, 2012 ); ARF6 and ARF8 promoted jasmonic acid production and flower maturation ( Nagpal et al, 2005 ); NPH4/ARF7 and ARF19 controlled leaf expansion and lateral root growth ( Okushima et al, 2005 ; Wilmoth et al, 2005 ). In tomato, SlARF2 regulated lateral root formation and flower senescence ( Ren et al, 2017 ); ARF4 controlled sugar metabolism ( Sagar et al, 2013 ); ARF10 increased chlorophyll and sugar accumulation during fruit development ( Mei et al, 2018 ); ARF5 regulated fruit set and development ( Liu et al, 2018 ). However, the roles of ARFs in plant carotenoid biosynthesis and abiotic stress responses are rarely known to date.…”
Section: Introductionmentioning
confidence: 99%
“…However, many GAs biosynthesis/signalling‐deficient maize ( Zea mays ) mutants have pleiotropic phenotypes that are detrimental to the crop yield (Li et al., 2019). Bioactive GAs are biosynthesized by a complex pathway, and have a profound influence on plant growth and development, including seed germination and development (Yamaguchi, 2008), stem elongation (Zhao et al., 2017), leaf expansion (Li et al., 2012), flower development and fruit set (Liu et al., 2018), root growth (Ubeda‐Tomás et al., 2008) and regulation of fertilization (Dorcey, Urbez, Blázquez, Carbonell, & Perez‐Amador, 2009). GAs biosynthesis and signalling pathways have been studied in various plant species, such as Arabidopsis (Yamaguchi et al., 2014), rice (Spielmeyer, Ellis, & Chandler, 2002; Tang et al., 2018), maize (White, Proebsting, Hedden, & Rivin, 2000; Zhang, Wang, Zhao, Zhang, & Li, 2019), wheat (Flintham, Börner, Worland, & Gale, 1997; Guo et al., 2018) and tomato (De Jong, Mariani, & Vriezen, 2009).…”
Section: Introductionmentioning
confidence: 99%